Erenköy Zihni Paşa Külliyesi ve kent dokusuna etkisi - Eroğlu, Serpil (My University, 2025)
Erenköy Zihni Paşa Külliyesi, II. Abdülhamid döneminin önde gelen devlet adamlarından, Mustafa Zihni Paşa tarafından inşa ettirilmiştir. Mimarının Mehmed Vedat Tek olduğu düşünülmektedir. Kitabelerdeki imzalarından hareketle hat sanatkârı ise Sami Efendi’dir. 1902-1903 (H.1320) yıllarına tarihlenen külliye, cami, mektep, dükkânlar, şadırvan, hazire imam-müezzin lojmanları ve meşrutalarının bulunduğu yapılar grubunu kapsamaktadır. Banisi, mimarı, hattatı ile öne çıkan külliye, yapılan onarımlarla belli ölçülerde özgünlüğünü yitirse de Erenköy’ün merkezinde hem semtin mekânsal gelişimine etkisi hem de Osmanlı son dönem eserlerinden biri olarak mimari açıdan önemli bir yere sahiptir. Erenköy tren istasyonunun karşısına konumlandırılmış külliye, aynı dönem banliyö hattı üzerinde inşa edilmiş, Bostancı, Suadiye, Göztepe, Kızıltoprak, Bakırköy, Yeşilköy’de olduğu gibi semtin sosyal ve ticari hayatını şekillendirmiştir. İkametlerin artmasıyla ileride oluşacak mahallelerin ilk çekirdeğini oluşturmuş ve semtin merkezi konumuna gelmişlerdir. Günümüzde de aynı işlevini sürdüren bu külliyeler inşa edildikleri semtlere değer kazandırmaktadır.

The Zihni Pasha Complex in Erenköy was commissioned by Mustafa Zihni Pasha, one of the prominent statesmen of the reign of Sultan II. Abdulhamid. The architect is believed to be Mehmed Vedat Tek. While the calligrapher is thought to be Sami Efendi, based on the inscriptions found on the buildings. Dated to 1902-1903 (1320 AH), the complex consists of a mosque, a primary school, shops, a fountain, residential lodgings for the imam and muezzin, annex buildings and a small cemetery where Mustafa Zihni Pasha and his wife, Emine Nazire Hanım, are buried. Despite having undergone restorations that partially compromised its originality, the complex stands out due to its founder, architect, and calligrapher, and maintains a significant position in Erenköy both for its architectural value as a late Ottoman structure and its influence on the spatial development of the neighborhood. Located directly opposite the Erenköy railway station, the complex was established along the same suburban railway line as other important districts such as Bostancı, Suadiye, Göztepe, Kızıltoprak, Bakırköy, and Yeşilköy. Similar to these districts, it played a formative role in shaping the social and commercial life of the area, laying the foundations of future neighborhoods as residential density increased and contributing to the emergence of a local urban center. Today, such complexes continue to serve similar functions and add historical and cultural value to their respective districts.
Keywords: banliyö; Cities and towns; complex (külliye); Erenkoy (Istanbul, Turkey); Erenköy; Erenköy (İstanbul, Türkiye); istasyon; kent dokusu; külliye; Social aspects; Sosyal yönleri; station; suburban railway; Şehirler ve kasabalar; urban fabric; Vedat Tek; Zihni Pasha; Zihni Paşa